Innovation for development and the role of government : (World Bank, 2009)
Innovation is the key determinant of growth and competitiveness. Increasing a country s overall innovation capabilities and creating a sound and efficient national innovation regime help to increase the quality and sustainability of economic development and boost a country s core competitiveness. In a world with expanding economic globalization, all countries are faced with opportunities and challenges. The hope is that they will cooperate to promote the healthy and harmonious development of the world economy, and this book takes a step in that direction. Innovation for Development and the Role of Government is organized around three themes: The relationship between innovation, competitiveness, and development; innovation and financial sector development; and innovation and government policies in China. It analyzes the nature of innovation and its role in economic development and competitiveness, and it offers practical policy options for decision makers, especially those in China. Throughout the volume, the authors argue that the concept of innovation encompasses not only the technological but also the non-technological forms. Technological innovation refers to the diffusion into the economy of new products and services of a technological nature. Non-technological innovation refers to advances in organizations or institutions, such as new management strategies or improved approaches to communications. Innovation is important for the service sectors, such as finance and public services, as well as for the production sectors, where technologies play a crucial role. This book will be a fascinating read for those involved or interested in business economics, finance, government, innovation, public policy, taxes, technology, or East Asia.